A correlational study of multicultural competency and self-efficacy in dealing with legal and ethical issues - Subarimaniam, Neerushah; Zakaria, Noor Syamilah; Wan Jaafar, Wan Marzuki (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Value helps counselor to navigate the challenges of being a professional helper. The evolution and integration of multicultural counseling have been mushrooming in a number of research fields. Multicultural competency is one’s awareness, knowledge, and skills about various cultures. While self-efficacy is an individual’s beliefs regarding his or her ability to accomplish a task successfully. The purpose of this study is to examine the relationship between multicultural competency and trainee counselors’ self-efficacy in dealing with legal and ethical issues. One hundred and forty eight respondents from three private universities in Malaysia participated in the study through simple random cluster sampling. There were a total of two instruments used to measure perceived multicultural competency and self-efficacy respectively. The data was analyzed using Pearson Correlation. Correlation analysis revealed that there is positive relationship between perceived multicultural competency and self-efficacy (r = 0.418, p < .01). The strength of relationship or the coefficient of r value between perceived multicultural competency and self-efficacy reflects a substantial relationship. Hence, this study is vital as it provides the idea of incorporating value in the process of shaping counselors who eventually will be able to deal with legal and ethical issues.